Manchurian candidate [videorecording (DVD)] - Frankenheimer, John, 1930-2002; Sinatra, Frank, 1915-1998; Harvey, Laurence; Lansbury, Angela, 1925- (MGM Home Entertainment, 2004)
A decorated Korean War veteran has been brainwashed to commit political assassinations, his old military commander begins to suspect and must stop him.